2014
DOI: 10.15760/comminfolit.2014.8.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Archival Intelligence: A Collaboration Between Library Instruction and Archives

Abstract: Although recent archival scholarship promotes the use of primary sources for developing students' analytical research skills, few studies focus on standards or protocols for teaching or assessing archival instruction. Librarians have designed and tested standards and learning assessment strategies for library instruction, and archivists would do well to collaborate with and learn from their experience. This study examines lessons learned from one such collaboration between an instructional services librarian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Although the ACRL Information Literacy Standards for Higher Education have been widely adopted and incorporated across disciplines, research in library science has much work to do in considering instructional strategies for connecting students to primary source materials. As Hensley, Murphy, and Swain (2014) note, "the social sciences and humanities are just beginning to explore ways in which undergraduates can contribute to knowledge in a discipline by asking original research questions, examining primary sources and creating new content" (97). In 2001, the ACRL formed a Task Force on Special Collections that was charged with defining core competencies, but these competencies are still being discussed and reviewed and aligned with the ACRL Framework (Association of College and Research Libraries 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ACRL Information Literacy Standards for Higher Education have been widely adopted and incorporated across disciplines, research in library science has much work to do in considering instructional strategies for connecting students to primary source materials. As Hensley, Murphy, and Swain (2014) note, "the social sciences and humanities are just beginning to explore ways in which undergraduates can contribute to knowledge in a discipline by asking original research questions, examining primary sources and creating new content" (97). In 2001, the ACRL formed a Task Force on Special Collections that was charged with defining core competencies, but these competencies are still being discussed and reviewed and aligned with the ACRL Framework (Association of College and Research Libraries 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The archives is then positioned at the center of an interdisciplinary and collaborative campus, a place that is particularly well-suited to the mission of community colleges like QCC. Hensley, Murphy, and Swain (2014) have argued that "students' exposure to archives through archival instruction can develop critical thinking, writing skills, and even improve communication skills through the experience of negotiating a successful research experience" (104 and 108). Yakel and Torres (2003) have found that" students interpreted the concepts introduced in an orientation to the College Archives as having applicability beyond the walls of the archives, having linked them to skills that are valuable for other research and writing assignments" (69).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many public libraries, too, retain their own genealogy sections and experts. Previous research has also shown that novice archives users have trouble distinguishing libraries from other public institutions like archives, historical societies, local museums, and newspaper archives (Hensley et al, 2014). In a time when users often feel adrift in huge swathes of digital information, it can be reassuring for overwhelmed beginners to have instructors emphasize the importance of nearby institutions that facilitate local research.…”
Section: Frame #1: Discovery and Accessmentioning
confidence: 99%
“…At the University of Illinois, for example, archivists conducted a course instruction session in the University archives' student life and culture archival program providing a brief description of the archives' purpose and founding, and an overview of the type of archival materials held by the archives. 22 If professional education is not offered, it has the potential to have a negative impact on the growth of a profession that is still not well understood in society. 23 The recent developments in the use of archival resources in schools have some useful lessons for archivists.…”
Section: Educational Program For Archives and Records Managementmentioning
confidence: 99%